The Fundamental Strategies that will Drive Higher Educational Sector Towards Digital Transformation in Industry 4.0 - David Mhlanga (Emerging Science Journal, 2023)
Digital transformation is the coordination of digital technologies with organizational aspects and human variables in a specific setting. It goes beyond simply implementing a technology solution. Additionally, it calls for the thoughtful and complete application of digital technology to the creation of new skills and theoretical frameworks. The goal of the current study is to examine the basic practices that will propel Industry 4.0's digital transformation of the educational sector. Utilizing a qualitative research approach that included a comparison and analysis of the relevant body of earlier work, the study discovered that digital transformation in education can be driven by several factors, including campus safety, data security, student achievement, strategy, data enablement, student-cantered services, cost and availability, digital integration, and artificial intelligence. The study concluded with a variety of strategies that can aid in the digital transformation of universities and other institutions of higher learning, like establishing a solid foundation for information and communication technology systems and delivering cyber security that is up to date with current best practices, among the many strategies suggested. Doi: 10.28991/ESJ-2023-SIED2-010 Full Text: PDF